Antiangiogenic Triterpenes Isolated from Chinese Herbal Medicine Actinidia chinensis Planch - Zhu, Wen-Jun; Yu, De-Hong; Zhao, Mei; Lin, Meng-Gan; Lu, Qin; Wang, Qi-Wei; Guan, Ying-Yun; Li, Gui-Xiu; Luan, Xin; Yang, Yi-Fang; Qin, Xue-Mei; Fang, Chao; et al. (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Actinidia chinensis Planch. is a famous Chinese herbal medicine to treat many diseases such as cancers. Triterpenes, polyphenols and anthraquinones are normally considered as the main constituents for its effects. In this study, eleven known triterpenes were isolated from the root of Actinidia chinensis., and were examined for its antiangiogenic activities. Their structures were elucidated by comprehensive spectroscopic methods, including IR, UV, HR-ESI-MS, and 1D and 2D NMR techniques. The eleven compounds are following: 2α,3α,19-trihydroxyurs-12-en-28-oic acid (1), 2α,3β-dihydroxyurs-12-en-28-oic acid (2), 2α,3α,23-trihydroxyurs-12-en-28-oic acid (3), asiatic acid (4), ursolic acid (5), 2α,3β,19,24-tetrahydroxyurs-12-en-28-oic acid (6), 2α,3β,19-trihydroxyolean-12-en-28-oic acid (7), 2α,3α,24-trihydroxyolean-12-en-28-oic acid (8), oleanolic acid (9), 3β-O-acetyloleanolic acid (10), 2α,23-dihydroxylmicromeric acid (11). All these compounds were evaluated with respect to their antiangiogenic activities utilizing the assays of human umbilical vein endothelial cells (HUVEC) proliferation and tube formation and Ursolic acid (used as control) and compounds 2, 3, 4, and 8 exhibited significant, dose-dependently, antiangiogenic activity in the tested concentration range. Our findings suggest that antitumor action of Actinidia chinensis Planch. is partly via inhibiting tumor angiogenesis by triterpenes, and compounds 2, 3, 4, and 8 as the novel potential antiangiogenic agents are worthy of further translational research.
Keywords: Antiangiogenic activity